Actualization of Religious Moderation Content Strategic Plan at State Islamic University - Wulandari, Widya; Sari, Dwi Wulan (Tribakti: Jurnal Pemikiran Keislaman, 2023)
This paper aims to describe religious moderation strategic plan as one of the primary programs at a state Islamic University. The research used a literature study, exploring data sources such as religious moderation strategic plan documents and state Islamic University website news regarding religious moderation. The research found the actualization of the religious moderation strategic plan implemented in the university environment and the academic community generally through news dissemination on the university's official website. There are six implementation strategies; 1). Facilitate the preparation of religious literacy according to local wisdom in electronic form; 2). Strengthen religious moderation content in matters of belief and character; 3). Increase religious extracurricular activities; 4). Improve the quality of tolerant and ethical conduct of students, educators, and other educational personnel; 5). Formation of working groups to disseminate concepts, guidelines, and implementation strategies and investigate the contents of the literature on religious moderation; 6). Improve the education system and staff's ability to investigate and implement models of religious moderation practice. The research findings indicate strategic plan elaborates the formulation of the university's vision and mission, which is ready to guide university leaders in fulfilling their mission and realizing their vision.